Representation and Legislative Functions of Women in the Regional People's Representative Council (DPRD) of Lamongan Regency - Erna Sujarwati; Dhia Al Uyun; Alifiulahtin Utaminingsih (Faculty of Law, Universitas Pekalongan, 2025)
The role of women legislators cannot be maximized if the quantity of women legislators is still low. In the DPRD of Lamongan Regency, out of 50 DPRD members, 11 are female legislators. Seeing the affirmative representation of women at 30%, the Lamongan district DPRD is still at 22%. Looking at the existing human resources of the 11 women legislators, have they carried out their legislative functions in accordance with their roles and functions? The purpose of this research is to find out the roles, constraints, and efforts to overcome obstacles to female legislators in carrying out legislative functions in the Lamongan Regency DPRD for the 2019-2024 period. The method used in this research is descriptive qualitative. In this study, it was found that from the three dimensions of roles expressed by Soerjono Soekanto, namely norms, individual concepts of society as an organization, and none of the behaviors are optimal. The conclusion of this study is that the role of women councilors in carrying out the legislative function in the DPRD of Lamongan Regency has not been maximized. Suggestions that can be put forward after conducting the research are that female council members are expected to be more active in maximizing their role at every meeting, female council members must make constraints a motivation for achievement and motivation for self-improvement to further develop, and female council members are given additional education programs about law and legislation in order to understand and maximize its role in carrying out legislative functions.